DEVELOPMENT OF CONCENTRATE-COMBINED SILAGE TECHNOLOGY FOR SUSTAINABLE WASTE MANAGEMENT AND ENHANCED GOAT PRODUCTIVITY IN KAHURIPAN URBAN VILLAGE - Wijayanti, Dwi; Fitria, Anita Dwy; Hikmatyar, Missi; Rahwana, Kusuma Agdhi; Nuranisa, Rini; Kamila, Ashila Rahmani; Septian, Fazril; Triyawan, Yuda Yudis (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
The sustainability of small ruminant farming in developing regions is often constrained by feed scarcity during the dry season, low animal productivity due to unbalanced nutrition, and ineffective agricultural waste management. This program addressed these challenges by implementing a concentrate-combined silage technology within the Farmers Group (Poktan) and Women Farmers Group (KWT) in Kahuripan Urban Village. The primary objective was to transform abundant local corn stover into high-quality, stable animal feed. A quasi-experimental (pretest-posttest) design was employed to evaluate the intervention's effectiveness. Results indicated a statistically improvement in the participants' knowledge regarding nutrition and silage technology (2.84 and 2.7 for KWT and Poktan, respectively). The resulting silage, enriched with concentrate, demonstrated optimal fermentation success, confirmed by achieving an pH range is 3.8 and favorable physical characteristics. Crucially, the introduction of this enriched silage into the feeding regimen of goats at Poktan led to a higher Average Daily Gain (ADG) compared to the traditional forage-only diet, thereby enhancing livestock productivity and resolving the problem of nutrient deficiency. This technology offers a sustainable, dual-benefit strategy by simultaneously converting agricultural by-products into a reliable feed source, ensuring year-round feed security, and improving the economic viability of small-scale goat farming.